Association of different bioimpedanciometry estimations of muscle mass with functional measures. Issue 7 (21st April 2019) - Bahat, Gulistan; Kilic, Cihan; Ilhan, Birkan; Karan, Mehmet A; Cruz‐Jentoft, Alfonso
Abstract : Aim: To investigate the muscle mass adjustment technique that best correlates with functional measures. Methods: A cross‐sectional study was designed. Community‐dwelling older adults aged ≥60 years were assessed for body composition and functional measures between November 2012 and July 2017 in the geriatric outpatient clinic of a university hospital. Body composition was assessed with bioimpedance analysis. Skeletal muscle mass (SMM) was adjusted by height 2, weight or body mass index (BMI). Functional and disability measures included handgrip strength assessed by a Jamar hydraulic hand dynamometer, gait speed by 4‐m usual gait speed, frailty by the Fatigue, Resistance, Ambulation, Illnesses and Loss of Weight scale score, activities of daily living (ADL) and instrumental ADL scores. Nutrition was evaluated by the Mini Nutritional Assessment – Short Form. Results: A total of 1437 older adults (458 men, 979 women) with a mean age of 74.6 ± 7.0 years were included. The prevalences of low muscle mass were 2.4%, 47.8% and 20.3% when SMM was adjusted by height 2, weight and BMI, respectively. Multivariate analyses adjusted for age, number of diseases, drugs and the Mini Nutritional Assessment – Short Form score revealed that when the SMM was adjusted by BMI, low muscle mass showed better associations with grip strength, gait speed, ADL, instrumental ADL and frailty than the height 2 or the weight‐adjusted SMM. Conclusions: SMM adjustment by BMI to designate low muscle mass was better associated with functional and disability measures than adjustment by height 2 and weight. The present results put forward the SMM index (by BMI) as the best adjustment method for SMM. These findings might be relevant for defining both sarcopenia and malnutrition.Geriatr Gerontol Int 2019; 19: 593–597 .